A Benchmark Visit to PSM UMP for The Bachelor of Applied Science In Data Analytics with Honors Programme by The College of Computing, Informatics and Media Studies of Uitm Terengganu Branch, Kuala Terengganu Campus - Siti Zanariah, Satari (Pusat Sains Matematik UMPSA, 2023)
A benchmark visit to PSM UMP for the Bachelor of Applied Science in Data Analytics with Honors programme by the UiTM College of Computing, Informatics and Media Studies, Terengganu Branch, Kuala Terengganu Campus was held on 22 June 2023, Thursday.